Maximum Likelihood Estimation of Tornqvist Demand Equations - Fisk, P. R. (Review of Economic Studies, 1958)
Journal Article Maximum Likelihood Estimation of Törnqvist Demand Equations Get access P. R. Fisk P. R. Fisk Aberdeen Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 26, Issue 1, October 1958, Pages 33–50, https://doi.org/10.2307/2295856 Published: 01 October 1958